PENINGKATAN HASIL BELAJAR LOMPAT TINGGI MELALUI MEDIA GAMBAR DAN MODIFIKASI MISTAR PADA SISWA SD - Amon, Amon; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:Problems in research is whether media pictures and modification bar can improve learning outcomes students vi of public school 07 terati kabupaten sanggau . Methods used research ptk with the sample using a technique total of sampling , all students a must as many as 14 students consisting of 10 students son and 4 students daughter . Means study results the high jump through the pictures and modification bar increased e ; 1 ) study results that is cycle i the average 35,71 % and cycle ii the average 92,86 % , on learning cycle i the average 56,79 % and cycle ii the average 82,50 % , 2 ) aspects psychomotor and cognitive , cycle i the average 57,14 % and 58,04 % and cycle ii the average 82,14 % and 92,86 % .Means study results the high jump through the pictures and modification increased the effectiveness of bar.Keywords: soccer, goalkeeper reflective, cognitive, affective, psychomotor.